2014
DOI: 10.1364/boe.5.001173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adaptive optics scanning light ophthalmoscopic fluorescein angiography and offset pinhole imaging

Abstract: Recent advances to the adaptive optics scanning light ophthalmoscope (AOSLO) have enabled finer in vivo assessment of the human retinal microvasculature. AOSLO confocal reflectance imaging has been coupled with oral fluorescein angiography (FA), enabling simultaneous acquisition of structural and perfusion images. AOSLO offset pinhole (OP) imaging combined with motion contrast post-processing techniques, are able to create a similar set of structural and perfusion images without the use of exogenous contrast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 38 publications
1
44
0
1
Order By: Relevance
“…In one patient with a central retinal vein occlusion, they showed regression of a microaneurysm in response to VEGF treatment. A related paper reporting on the same patient presented 5 different ways the AO can visualize an individual microaneurysms (Chui et al 2014). Fig.…”
Section: 0 How Is Aoslo Being Used Clinically?mentioning
confidence: 99%
See 1 more Smart Citation
“…In one patient with a central retinal vein occlusion, they showed regression of a microaneurysm in response to VEGF treatment. A related paper reporting on the same patient presented 5 different ways the AO can visualize an individual microaneurysms (Chui et al 2014). Fig.…”
Section: 0 How Is Aoslo Being Used Clinically?mentioning
confidence: 99%
“…Scale bar is 0.5 deg. (B) from (Chui et al 2014) This figure shows a close up of one location indicated by the dashed white box in (A) imaged using in 4 different modes in the same AOSLO system (B.i) fluorescein angiography (B.ii) confocal (B.iii) motion contrast (B.iv) offset pinhole. A video recorded with offset pinhole AOSLO can be seen here.…”
Section: Figurementioning
confidence: 99%
“…Fluorescein angiography (FA), coupled with confocal AOSLO, has enhanced the success of imaging the retinal microvasculature of the macula (Fig. 1b) and peripapillary retina [21, 22]. Although confocal AOSLO FA is considered safe and has been used to show perfusion and non-perfusion of the retinal capillaries in healthy controls and patients with vasculopathies [2325], it requires an additional light source for fluorescein excitation and administration of oral fluorescein, making it more invasive with some risk of patient discomfort and potential side effects such as nausea and itching.
Fig.
…”
Section: Reviewmentioning
confidence: 99%
“…Microvascular perfusion maps are generated by extraction of moving elements from registered nonconfocal AOSLO videos, such as the intravascular flow of erythrocytes against the background of static tissue [2]. Nonconfocal AOSLO imaging provides structural images and perfusion maps comparable to those of confocal AOSLO FA with additional structural information such as fine structural components of vascular walls [22]. Figure 2 shows in vivo visualization of retinal vascular mural cells (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…The early signs of diabetic retinopathy as manifested in retinal images include micro-aneurysms, hemorrhages and exudates. Clinicians commonly use retinal images for the screening differential diagnosis of retinal diseases such as retinal edema, diabetic retinopathy, age-related macular degeneration, malarial retinopathy, glaucoma, cataracts, exudates, lesions, prediction of strokes in hypertension patients and so on [2][3][4].…”
Section: Introductionmentioning
confidence: 99%